2021
DOI: 10.1371/journal.pone.0249146
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-212-5p and its target PAFAH1B2 suppress vascular proliferation and contraction via the downregulation of RhoA

Abstract: Vascular remodeling and contraction contribute to the development of hypertension. We investigated the role of miR-212-5p and its downstream target in vascular smooth muscle cell (VSMC) proliferation, migration, and contraction. MicroRNA microarray and PCR analyses showed that miR-212-5p expression was increased with angiotensin II treatment in vivo and in vitro. Moreover, miR-212-5p mimic treatment attenuated and miR-212-5p inhibitor treatment increased VSMC proliferation and migration. Additionally, miR-212-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Previous studies have shown that the high expression of miR-212-5p can downregulate RhoA through its target PAFAH1B2 to inhibit vascular proliferation and contraction (29). Our study revealed a significant decrease in the expression level of hsa-miR-212-5p in exosomes from T2D patients.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that the high expression of miR-212-5p can downregulate RhoA through its target PAFAH1B2 to inhibit vascular proliferation and contraction (29). Our study revealed a significant decrease in the expression level of hsa-miR-212-5p in exosomes from T2D patients.…”
Section: Discussionsupporting
confidence: 59%
“…The alpha2 catalytic subunit of the cytoplasmic platelet-activating factor I (PAF) acetylhydrolase (PAF-AH (I)) isotetramerase can catalyze the hydrolysis of the sn-2 acetyl group of PAF and regulate its activity . A study has pointed out that PAFAHB12, the downstream target of miR-212-5p, can suppress the proliferation of vascular smooth muscle cells and vascular contraction …”
Section: Resultsmentioning
confidence: 99%
“…46 A study has pointed out that PAFAHB12, the downstream target of miR-212-5p, can suppress the proliferation of vascular smooth muscle cells and vascular contraction. 47…”
Section: Characterization and Validation Of Novel Seps Found In The S...mentioning
confidence: 99%
“…miRNAs, a unique class of noncoding RNAs, can regulate their target genes at the transcriptional level, thereby participating in physiological activity and disease development. It has been widely reported that miR-212-5p plays different roles in various diseases, such as diabetes mellitus, colorectal cancer liver metastasis, and hypertension. Even in fibrotic diseases, the functions of miR-212-5p are different. In cardiac fibrosis, miR-212-5p targets c-Myc and NLRC5, ultimately inhibiting the proliferation and activation of fibroblasts and collagen deposition. , In contrast, a study showed that miR-212-5p contributed to the progression of renal interstitial fibrosis by regulating a hypoxia-inducible factor 1-α inhibitor in the kidney tissues of UUO mice .…”
Section: Discussionmentioning
confidence: 99%